Smart Governance: A Study of the Jakarta Smart City During the Covid-19 Pandemic - Firman, Firman; Sumatono, Sumatono; Muluk, MR Khairul; Setyowati, Endah (KnE Social Sciences, 2022)
This study focused on the problems of smart city governance in Indonesia, especially in the implementation of smart governance during the COVID-19 pandemic in the Jakarta Smart City. Smart governance can help provide information and influence governance in handling COVID-19. This study examined the development of smart city governance in contributing to the handling of COVID-19, especially in providing smart information to stakeholders to improve the effectiveness of policies. This study also investigated the development of technological, institutional and human capital aspects. Data were collected from websites and smart city media in Jakarta such as Citizen Relations Management, Open data, Qlue applications, Jakarta Kini ( Jaki), and the Jakarta Smart City portal. The results showed the technical aspects that influenced the development of smart city governance, in terms of the basis for digitizing government that led to urban intelligence, as well as the institutional and human capital aspects which were also needed to support the success of the smart city. Keywords: smart city governance, Jakarta smart city, COVID-19 pandemic